Immunohistochemical evaluation of glucose transporter protein-1 density in the placenta in preeclampsia patients and its association with intrauterine growth retardation: GLUT1 density and IUGR - Yavuz, Adem; Dolanbay, Mehmet; Akgun, Hulya; Yazici Ozgun, Gulcan; Cagli, Fulya; Ozgun, Mahmut Tuncay (Journal of Surgery and Medicine, 2022)
Background/Aim: Preeclampsia (PE) complicates 2–8% of all pregnancies worldwide. Placental malperfusion and dysfunction are observed in PE. The supply of glucose, the main energy substrate for the fetus and placenta, is regulated by placental expression and activity of specific glucose transporter proteins (GLUTs), primarily GLUT1. GLUT1 expression is affected by uteroplacental malperfusion and oxidative stress, which are important components of PE. Very few studies have investigated GLUT1 expression in preeclamptic placentas. In this study, we aimed to compare GLUT1 staining intensity in the terminal villi of the placenta in healthy subjects and patients with E-PE or L-PE and determine whether there was a relationship between GLUT1 staining intensity and IUGR. Methods: This case-control study was carried out in our hospital’s gynecology and obstetrics clinic, a tertiary center for perinatology cases. A total of 94 placentas, 47 of which were preeclamptic and 47 were from uneventful pregnancies (controls), were included in the study. PE was diagnosed according to the American College of Obstetrics and Gynecologists 2019 diagnostic criteria for gestational hypertension and PE. Placentas in the control group were obtained from pregnancies without maternal, placental, or fetal pathology and resulted in spontaneous idiopathic preterm or term delivery. The PE group was divided into two subgroups as early onset PE (E-PE [≤33+6 gestational week]) and late-onset PE (L-PE [≥34+0 gestational week]), according to the gestational week of PE onset. Sections prepared from placental tissues were stained for GLUT-1 by immunohistochemical method. Slides were evaluated by light microscopy, and each slide was scored from 0 to 4 to determine the staining intensity. The results were compared between the control and PE group/PE sub-groups. Results: GLUT1 scores were significantly higher in both early- and late-onset PE subgroups compared to controls (P < 0.001 for both). In the late-onset PE subgroup, GLUT1 scores were significantly higher in those with severe PE features than those without them (P = 0.039). While intrauterine growth restriction (IUGR) was not found in any cases in the control group, IUGR was present in 11 (23.4%) of 47 pregnant women with PE, including eight (53.3%) of the 15 pregnant women with early-onset PE and 3 (9.38%) of the 32 pregnant women with late-onset PE. GLUT1 scores were similar in placentas obtained from pregnant women who had PE with and without IUGR (P = 0.756). In the late-onset PE subgroup, GLUT1 scores were correlated negatively with maternal body mass index (r = -0.377, P = 0.033) and positively with placental weight-to-fetal weight ratio (r = 0.444, P = 0.011). Conclusions: Our findings show that GLUT1 expression might be increased due to placental adaptation to new conditions in PE and, thus, is unlikely to be the main factor in PE-related IUGR.